Ultrahigh frequency lensless ultrasonic transducers for acoustic tweezers application1. Issue 3 (16th October 2012) - Lam, Kwok Ho; Hsu, Hsiu‐Sheng; Li, Ying; Lee, Changyang; Lin, Anderson; Zhou, Qifa; Kim, Eun Sok; Shung, Kirk Koping
Abstract Similar to optical tweezers, a tightly focused ultrasound microbeam is needed to manipulate microparticles in acoustic tweezers. The development of highly sensitive ultrahigh frequency ultrasonic transducers is crucial for trapping particles or cells with a size of a few microns. As an extra lens would cause excessive attenuation at ultrahigh frequencies, two types of 200‐MHz lensless transducer design were developed as an ultrasound microbeam device for acoustic tweezers application. Lithium niobate single crystal press‐focused (PF) transducer and zinc oxide self‐focused transducer were designed, fabricated and characterized. Tightly focused acoustic beams produced by these transducers were shown to be capable of manipulating single microspheres as small as 5 µm two‐dimensionally within a range of hundreds of micrometers in distilled water. The size of the trapped microspheres is the smallest ever reported in the literature of acoustic PF devices. These results suggest that these lensless ultrahigh frequency ultrasonic transducers are capable of manipulating particles at the cellular level and that acoustic tweezers may be a useful tool to manipulate a single cell or molecule for a wide range of biomedical applications. Biotechnol. Bioeng. 2013; 110: 881–886. © 2012 Wiley Periodicals, Inc.